The assessment of musculoskeletal disorders, quality of life, and comorbidities in older people in Bangladesh - Sharmila Jahan; Sharmila Jahan; Rabiul Islam; Tania Rahman; Md. Feroz Kabir; Md. Waliul Islam; Kabir Hossain; K. M. Amran Hossain; Md. Zahid Hossain; Ehsanur Rahman; Sonjit Kumar Chakrovorty; Sonjit Kumar Chakrovorty; et al. (Frontiers Media S.A., 2023)
Musculoskeletal disorders are debilitating conditions that significantly impact the state of health, especially in older people. The study, which employed a cross-sectional design and practical sampling, included 206 participants among them 124 (62.2%) were men and 82 (39.8%) were women, from all over Bangladesh with musculoskeletal issues of varying severity and impact. The mean age of the participants was 64.9 (SD 4.3). The study was carried out between January and June of 2022. The majority of participants experienced musculoskeletal pain. Back pain was the most commonly complained of symptom among the participants (74.9%). It was also common to have limited mobility as a result of arthritic change, which eventually affected daily activities like taking care of oneself. To improve the health of the older adult population, more studies must be conducted to identify the many factors that contribute to musculoskeletal issues. The development of effective prevention and rehabilitation programs must then be based on this knowledge.